2014
DOI: 10.1039/c4cc03153a
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent interaction-assisted polymeric micelles for controlled drug delivery

Abstract: Polymeric micelles are one of the most promising nanovehicles for drug delivery. In addition to amphiphilicity, various individual or synergistic noncovalent interplays including strong hydrophobic, electrostatic, host-guest, hydrogen bonding, stereocomplex and coordination interactions have been recently employed to improve the physical stability of micelles, and even provide them with certain intelligences or bioactivities. Through the ingenious designs and precise preparations, many noncovalent-mediated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
133
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 169 publications
(205 reference statements)
0
133
0
Order By: Relevance
“…Over the past decades, several nano-sized DDSs have been developed and applied by targeted drug delivery to cancer cells, such as liposomes, [4][5][6][7] polymeric micelles, [8][9][10][11] dendrimers, [12][13][14][15][16] carbon nanotubes, [17][18][19][20][21][22] inorganic nanoparticles, [23][24][25][26] and silica-based materials. [27][28][29][30][31] Among them, mesoporous silica nanoparticles (MSNs) have attracted much attention due to their unique physiochemical properties, such as large specific surface area and pore volume, controllable particle size, remarkable stability and biocompatibility, and high drug-loading capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, several nano-sized DDSs have been developed and applied by targeted drug delivery to cancer cells, such as liposomes, [4][5][6][7] polymeric micelles, [8][9][10][11] dendrimers, [12][13][14][15][16] carbon nanotubes, [17][18][19][20][21][22] inorganic nanoparticles, [23][24][25][26] and silica-based materials. [27][28][29][30][31] Among them, mesoporous silica nanoparticles (MSNs) have attracted much attention due to their unique physiochemical properties, such as large specific surface area and pore volume, controllable particle size, remarkable stability and biocompatibility, and high drug-loading capacity.…”
Section: Introductionmentioning
confidence: 99%
“…37 It is also investigated that the drug whose active site is covalently bound to the surface of NPs are observed not to undergo controlled drug release readily as compared with drugs encapsulated by following noncovalent interactions. 38 Therefore for controlled and targeted delivery, formulation of nanocarriers with noncovalent interactions may be the probable method of preserving the active ingredients and structural integrity of the materials as much as possible. Hence, the nonchemical methods adopted in this work follows simple ultrasonication, centrifugation, and controlled pH.…”
mentioning
confidence: 99%
“…It is worth mentioning that the fluorescence intensities of tumor and test organs were observed to fall in the free EPI group when the time extended from 6 to 12 h, while that in the mPEG-b-PGA/EPI group increased somewhat. The different changes indicated that the micellization was able to improve the pharmacokinetic character of free drug and made them metabolize longer [16,35]. More meaningfully, the tumor fluorescence intensity of mouse treated with mPEG-b-PGA/EPI for 6 h is stronger than that with free EPI, and the distinction was more obvious at 12 h post-injection.…”
Section: Improved Tissue Distribution and Enhanced Antitumor Efficacymentioning
confidence: 70%